Guinea-Bissau : First Review Under the Three-Year Arrangement Under the Extended Credit Facility and Financing Assurances Review-Staff Report; Staff Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Guinea-Bissau. (IMF Staff Country Reports; Country Report ;, 2010)
The paper highlights that Guinea-Bissau managed to maintain macroeconomic stability amid challenging political circumstances. The Executive Board agreed that the performance under the Extended Credit Facility (ECF)-supported program has been satisfactory in attaining substantial progress with structural reforms. They agreed that it has qualified for debt relief, including for topping-up assistance; the Board also stressed the need to maintain commitment to the successful implementation of economic reforms.